The cycle performance of high nickel cathode materials significantly enhanced by the LiAlO2@Al2O3 dual-modified coating. (20th January 2021) - Shan, Wei; Zhang, Hongxu; Hu, Chen; Zhou, Yu; Lam, Kwok-ho; Wang, Shaofeng; Hou, Xianhua
Highlights: LiAlO2 @Al2 O3 dual-modified coating is successfully coated on the surface of LiNi0.88 Co0.09 Al0.03 O2 . The coated NCA exhibits better cycle and rate performance at high current densities. The electrochemical performance at high cut-off voltages is effectively improved. The lithium ion diffusion capacity of the coated NCA is significantly improved. Abstract: The degradation of interface and crystal structure during the cycle seriously hinders the further development and application of high-nickel cathode materials. In order to solve this problem, we synthesize a Al2 O3 modified coating on LiNi0.88 Co0.09 Al0.03 O2 (NCA) cathode material particles. However, further research discovers that the coating is not composed of a single Al2 O3 as previously reported. On the contrary, a part of Al2 O3 in the inner layer of the coating near the host material may be induced to form a thin layer of LiAlO2 on the surface of the NCA, while the outer layer of the coating is still composed of Al2 O3 . This LiAlO2 @Al2 O3 dual-modified coating reveals a new surface coating structure. And the results show that the NCA material coated with the appropriate thickness of the coating has a first charge/discharge capacity of 242.1/210.3 mAh g −1 at a current density of 0.1 C (20 mA g −1 ). When the current density is increased to 1.0 C (200 mA g −1 ), the capacity retention rate is still 82.8% (62.6% of the pristine material) after 100 cycles. Even at a current density of 2.0 C, the discharge capacity is still 189.2 mAh g −1, which shows its better rate performance. The cycle performance and the capacity retention of materials at high currents are significantly improved. The study finds that LiAlO2 @Al2 O3 dual-modified coating has a positive effect on stabilizing the particle surface, resisting attacks from the electrolyte and improving the diffusion performance of Li +, which may be the reasons for the enhanced cycle stability and capacity retention of the material.